Parental leave: a policy evaluation of the Swedish daddy-month reform - John Ekberg; Rickard Eriksson; Guido Friebel (Institute for the Study of Labor (IZA), 2005)
Many countries are trying to incentivize fathers to increase their share in parental leave and in household work to improve female labor market opportunities. Our unique data set stems from a natural experiment in Sweden. The data comprises all children born before (control group) and after the reform (treatment group) in cohorts of up to 27,000 newborns, mothers and fathers. We find strong short term effects of incentives on male parental leave. However, we find no learning-by doing, or specialization, effects: fathers in the treatment group do not have larger shares in the leave taken for care of sick children, which is our measure for household work.
Keywords: J48; J13; J16; J22; 330; natural experiment; family benefits; gender and labor; incentives